Ultrasound to Improve the Safety and Efficacy of Lipofilling of the Temples. (11th March 2020) - Kadouch, Jonathan; Schelke, Leonie W; Swift, Arthur
Abstract: Background: Autologous fat is known for a reliable and natural safety profile, but complications do occur—even serious vascular adverse events. Objectives: The authors sought to examine doppler-ultrasound (DUS) imaging for the harvesting and subsequent facial implantation of autologous fat tissue. Methods: All patients underwent lipofilling treatment of the temporal fosse of the face. DUS examination was performed for preprocedural vascular mapping and imaging of previously injected (permanent) fillers. In addition, the injection of autologous fat was performed DUS-guided. Results: Twenty patients (all female; mean age, 57.9 years; range, 35-64 years). DUS examination showed that 16 of the 20 patients (80%) had been injected with resorbable or nonresorbable fillers elsewhere in the past. The temporal artery could be visualized and avoided in all cases. An average of 1.1 cc of autologous fat was injected in the temporal fossa per side. One case of edema and nodules was described, but no other adverse events were reported. Conclusions: The utilization of DUS can add valuable information to a lipofilling procedure and should be considered an integral part of a safe lipofilling treatment. Level of Evidence: 4: